PERANAN GOOD CORPORATE GOVERNANCE SEBAGAI PEMODERASI CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN - Zaky Machmuddah; Natalistyo T.A.H (Juara: Jurnal Riset Akuntansi, 2018)
Corporate social responsibility (CSR) that still creates problems for stakeholders is the main idea in this research. For example not the end of case PT. Lapindo and Freeport until now. Corporate social responsibility includes the relationship between the company and its stakeholders, therefore the company focuses not only on the single bottom line but rather on the triple bottom line. So with the implementation of CSR activities will improve the image of the company that will ultimately increase the value of the company. Implementation of CSR activities is a form of implementation of good corporate governance principle, because the company has realized a sense of concern on the social environment (Rustiarini, 2010). Finding empirical evidence on the role of CSR to increase corporate value with good corporate governance as moderator is the goal of this study. Mining companies listed on the Indonesia Stock Exchange (BEI) for the period 2012-2016 used as sample research. Annual report is used as a source of information extracting. Descriptive analysis with WarpPLS is a data analysis technique used in this research. The results show that CSR has an effect on corporate value and good corporate governance which is represented by independent board of commissioner and audit committee strengthen the influence of CSR on company value. The practical implication of this research is that every company must implement CSR because CSR plays a role to increase company value, as well as good corporate governance will strengthen the role of CSR in increasing company value.